2024
DOI: 10.1002/cptc.202400100
|View full text |Cite
|
Sign up to set email alerts
|

The Orthogonal α‐meso‐Linked bisBODIPY Photosensitizers Demonstrate Effective Two‐Photon Fluorescence Imaging and Photodynamic Therapy

Luying Guo,
Xing Guo,
Huiquan Zuo
et al.

Abstract: Hypoxic tumor microenvironments pose significant challenges to the clinical translation of cancer photodynamic therapy (PDT). While heavy atom‐free Type‐I boron dipyrromethenes (BODIPYs) photosensitizers can alleviate this challenge by reducing oxygen dependency, but they remain scarce. Herein, heavy‐atom‐free α,meso‐linked bisBODIPYs were designed and synthesized. These bisBODIPYs exhibit remarkable red‐shifted emission (λemmax ~670 nm), large Stokes shifts (~4480 cm‐1) and they are capable of producing both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…DFT and TD-DFT studies were in agreement with the experimental observations. Recently, such covalently linked BODIPY–BODIPY dyads 32 have been used for the generation of reactive oxygen species to test their ability as photosensitizers for therapeutic applications. Our preliminary studies also revealed that both triads 6 and 7 generate reactive oxygen species (ROS) when the triads in toluene were irradiated in the presence of TEMPO.…”
Section: Discussionmentioning
confidence: 99%
“…DFT and TD-DFT studies were in agreement with the experimental observations. Recently, such covalently linked BODIPY–BODIPY dyads 32 have been used for the generation of reactive oxygen species to test their ability as photosensitizers for therapeutic applications. Our preliminary studies also revealed that both triads 6 and 7 generate reactive oxygen species (ROS) when the triads in toluene were irradiated in the presence of TEMPO.…”
Section: Discussionmentioning
confidence: 99%